2013
DOI: 10.33899/edusj.2013.89973
|View full text |Cite
|
Sign up to set email alerts
|

Effect Zinc Ion Concentration on Structural and Optical Properties of ZnS Thin Films Prepared by Chemical Bath Deposition Technique

Abstract: 3 Zn(NO ) ‫ي‬ ‫ي‬ ‫ضر‬ ‫ي‬ ‫ضر‬ ‫ل‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ص‬ 2+ Zn ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ضرث‬ ‫ي‬ ) 2 ) 2 SC(NH ) ‫ر‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ضرل‬ ‫يل‬ ‫ي‬ ‫ي‬ ‫ضر‬ ‫ل‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ص‬ -2 S .) ‫ث‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ضل‬ ‫يز‬ ‫ي‬ ‫ي‬ ‫يي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ضر‬ ‫ل‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ض‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ع‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ 0.05M ‫ي‬ 0.1M ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ضري‬ ‫ية‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ضردص‬ ‫يص‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫عح‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ص‬ ‫ضر‬ ‫ي‬ . ‫يل‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ي‬ ‫ة‬ ‫ض‬ ‫أ‬ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Recently, it is reported that the boron-doped CdS samples can be deposited by USP technique using boric acid (H3BO3) as a dopant. It was found that borondoping is an alternative for decreasing the resistivity of CdS films (Ahmed & Dakhel 2012). CdS film is a II-VI compound polycrystalline semiconductor with a direct optical band gap of Eg=2.42 eV at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is reported that the boron-doped CdS samples can be deposited by USP technique using boric acid (H3BO3) as a dopant. It was found that borondoping is an alternative for decreasing the resistivity of CdS films (Ahmed & Dakhel 2012). CdS film is a II-VI compound polycrystalline semiconductor with a direct optical band gap of Eg=2.42 eV at room temperature.…”
Section: Introductionmentioning
confidence: 99%